ПОТЕНЦІЙНІ ЗАСОБИ ЕКРАНУВАННЯ МАГНІТНОГО ПОЛЯ ПІДЗЕМНИХ СИЛОВИХ КАБЕЛІВ У ПОЛІЕТИЛЕНОВИХ ТРУБАХ З КОМПОЗИ-ЦІЙНОГО МАГНІТНОГО МАТЕРІАЛУ - Кучерява, І.М. (Інститут електродинаміки НАН України, Київ, 2023)
The magnetic field of the medium- and high-voltage underground power cable line, laid in composite polyethylene pipes having magnetic properties, with the use of special loose-fill/fill-up soil of different dimensions (bulk) is studied by computer modeling. The pipes and additional soils around and near the cables are made of a composite material with effective magnetic properties and can act as a magnetic shield that reduces the level of the field on the ground. The efficiency of field shielding depending on the height and width of the composite loose-fill/fill-up soil is analyzed. The existence of the optimal not large (in height) fill-up soil for the best mitigation of the magnetic field on the ground directly above the cables and the influence of the width of the loose-fill/fill-up soils on the shielding efficiency are revealed. The characteristic features of the magnetic field distribution and the field level depending on the availability or non-availability of composite loose-fill soil are presented. The advantages of (trefoil) cable arrangement in one pipe with additional composite loose-fill and fill-up soil are shown. References 30, figures 5.